SARS-CoV-2 infection impairs NK cell functions via activation of the LLT1-CD161 axis - Lenart, Marzena; Górecka, Magdalena; Bochenek, Michal; Barreto-Duran, Emilia; Szczepański, Artur; Gałuszka-Bulaga, Adrianna; Mazur-Panasiuk, Natalia; Węglarczyk, Kazimierz; Siwiec-Koźlik, Andżelika; Korkosz, Mariusz; Łabaj, Paweł P.; Baj-Krzyworzeka, Monika; et al. (Frontiers in Immunology, 2023)
Introduction Natural killer (NK) cells plays a pivotal role in the control of viral infections, and their function depend on the balance between their activating and inhibitory receptors. The immune dysregulation observed in COVID-19 patients was previously associated with downregulation of NK cell numbers and function, yet the mechanism of inhibition of NK cell functions and the interplay between infected cells and NK cells remain largely unknown. Methods In this study we show that SARS-CoV-2 infection of airway epithelial cells can directly influence NK cell phenotype and functions in the infection microenvironment. NK cells were co-cultured with SARS-CoV-2 infected epithelial cells, in a direct contact with A549ACE2/TMPRSS2 cell line or in a microenvironment of the infection in a 3D ex vivo human airway epithelium (HAE) model and NK cell surface expression of a set of most important receptors (CD16, NKG2D, NKp46, DNAM-1, NKG2C, CD161, NKG2A, TIM-3, TIGIT, and PD-1) was analyzed. Results We observed a selective, in both utilized experimental models, significant downregulation the proportion of CD161 (NKR-P1A or KLRB1) expressing NK cells, and its expression level, which was followed by a significant impairment of NK cells cytotoxicity level against K562 cells. What is more, we confirmed that SARS-CoV-2 infection upregulates the expression of the ligand for CD161 receptor, lectin-like transcript 1 (LLT1, CLEC2D or OCIL), on infected epithelial cells. LLT1 protein can be also detected not only in supernatants of SARS-CoV-2 infected A549ACE2/TMPRSS2 cells and HAE basolateral medium, but also in serum of COVID-19 patients. Finally, we proved that soluble LLT1 protein treatment of NK cells significantly reduces i) the proportion of CD161+ NK cells, ii) the ability of NK cells to control SARS-CoV-2 infection in A549ACE2/TMPRSS2 cells and iii) the production of granzyme B by NK cells and their cytotoxicity capacity, yet not degranulation level. Conclusion We propose a novel mechanism of SARS-CoV-2 inhibition of NK cell functions via activation of the LLT1-CD161 axis.